2010
DOI: 10.1007/s00421-010-1681-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of training status and exercise modality on pulmonary O2 uptake kinetics in pubertal girls

Abstract: The influence of training status on the oxygen uptake (VO2) response to heavy intensity exercise in pubertal girls has not previously been investigated. We hypothesised that whilst training status-related adaptations would be evident in the VO2, heart rate (HR) and deoxyhaemoglobin ([HHb]) kinetics of pubertal swimmers during both lower and upper body exercise, they would be more pronounced during upper body exercise. Eight swim-trained (T; 14.2 ± 0.7 years) and eight untrained (UT; 14.5 ± 1.3 years) girls com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
29
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 62 publications
(100 reference statements)
3
29
2
Order By: Relevance
“…The significant influence of training status on the relative GET in Pre girls contrasts previous reports in prepubertal children (9,31,62), while the lack of training status effect in Pub girls disagrees with an earlier study in adolescents (27). No studies are available that have specifically investigated the influence of training status in Post girls, but the current findings differ from those in adults (6,47).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The significant influence of training status on the relative GET in Pre girls contrasts previous reports in prepubertal children (9,31,62), while the lack of training status effect in Pub girls disagrees with an earlier study in adolescents (27). No studies are available that have specifically investigated the influence of training status in Post girls, but the current findings differ from those in adults (6,47).…”
Section: Discussioncontrasting
confidence: 99%
“…The reason(s) for these contradictory results is (are) unclear; however, they do not support the concept of a maturational threshold. The faster MRT exhibited by the T girls in all three maturity groups during both exercise modalities agrees with studies reporting faster V O 2 kinetics in trained prepubertal children (62), pubertal adolescents, (27) and adults (1,17,24,37). The quantitative differences in SV according to training status in children are widely attributed to morphological adaptations of the myocardium, including an increased left ventricular dimension and mass and intraventricular and posterior wall thickness (e.g., Refs.…”
Section: Discussionsupporting
confidence: 87%
“…It has, however, previously been demonstrated that the menstrual phase has no effect on the p 2 o V  or HHb kinetics (Gurd et al 2007). The sample sizes were small, but were in accord with previous work published in this area (McNarry et al 2011;Winlove et al 2010). Furthermore, the lack of significant differences in HHb kinetics was offset by the large effect sizes.…”
Section: Discussionsupporting
confidence: 74%
“…Earlier evidence from cross-sectional studies seemed to indicate that exercise training had no effect in reducing the time constant of the fundamental phase of p 2 o V  kinetics in pre-pubertal children (Cleuziou et al 2002;Obert et al 2000). More recent cross-sectional studies, however, have demonstrated that systematic exercise training may result in a speeding of the fundamental phase of p 2 o V  kinetics in both children (Winlove et al 2010) and adolescents (Marwood et al 2010, McNarry et al 2011. Such discrepancies may be explained by the lack of congruence between the training and experimental exercise modality in the earlier studies (Cleuziou et al 2002;Obert et al 2000).…”
mentioning
confidence: 99%
“…In trained children, a faster heart rate response (Marwood et al 2010;McNarry et al 2011;Winlove et al 2010), which may provide a crude estimate of muscle blood flow kinetics (MacPhee et al 2005), and faster capillary blood flow kinetics have been shown (Marwood et al 2010). Although O 2 delivery is unlikely to be limiting in normal-weight, healthy children, whether an O 2 delivery limitation is present in obese children remains to be resolved.…”
Section: Discussionmentioning
confidence: 97%